2020
DOI: 10.1007/s00410-020-01720-1
|View full text |Cite|
|
Sign up to set email alerts
|

Rheology of melts from the colli albani volcanic district (Italy): a case study

Abstract: In this study the first viscosity measurements in the glass transition range of melts from highly explosive large-volume eruptions from the Colli Albani Volcanic District (CAVD) are presented. The magmas are ultrapotassic, rich in iron and CaO and characterised by a low silica content (< 45 wt%). Melt compositions range from tephri-phonolitic to foiditic. The Colli Albani eruptions appear anomalous since they produced a large volume of erupted material in spite of their silica undersaturated compositions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Geological importance for the PR and PN eruptions Kleest et al (2020) showed that the viscosities of the volatilefree melts of the Pozzolane Rosse and Pozzolane Nere event are higher than expected. They also demonstrated a viscosity decrease for the PR melt caused by assimilation of carbonate wall rock due to an enrichment in Ca 2+ , and an additional reduction in melt viscosity following leucite crystallisation.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Geological importance for the PR and PN eruptions Kleest et al (2020) showed that the viscosities of the volatilefree melts of the Pozzolane Rosse and Pozzolane Nere event are higher than expected. They also demonstrated a viscosity decrease for the PR melt caused by assimilation of carbonate wall rock due to an enrichment in Ca 2+ , and an additional reduction in melt viscosity following leucite crystallisation.…”
Section: Discussionmentioning
confidence: 84%
“…During the storage of the parental PR and PN magmas, crystal formation reaches fractions up to 60 vol% documented by pyroclastic products (Freda et al 2011). Kleest et al (2020) calculated a resulting viscosity increase up to two orders in magnitude for a leucite content of 56 vol% after a model from Caricchi et al (2007). Additionally, carbonate assimilation reaches values of 15 wt% (Iacono-Marziano et al 2007) which clearly exceeds the solubility of CO 2 in the PR melt (Schanofski et al 2019).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The Arrhenian equation should not be extrapolated linearly in temperature. Instead the configurational heat capacity and the Adam-Gibbs equation (Richet 1984) have been used to fit the viscosity data across of the entire temperature range: in order to calculate the temperature dependence of the viscosity at high temperatures; for A AG a constant, taken to be − 4.55 (see Giordano et al 2008;Kleest et al 2020 and references therein); B AG activation energy (J mol −1 ), S conf (T g 12) configuration entropy (J mol −1 K −1 ) at the temperature for which viscosity is 10 12 Pa s, C p conf the difference in ( 9) extrapolated glass heat capacity and relaxed melt heat capacity (J mol −1 K −1 ) at a temperature above the glass transition. This equation describes the viscosity-temperature behaviour of the melt from the temperature range of measurement to higher temperatures.…”
Section: Resultsmentioning
confidence: 99%